A change of habit : leaving behind my husband, career, and everything I owned to become a nun - Clare, Monica, Sister (Crown ; Sugar23, 2025)
"The Work shall be the Author's memoir, tracing her journey from a glamorous career in Hollywood to a convent in New Jersey, told with dry wit and her knack for one-liners, bringing alive her soulful story of finding solace in a sisterhood of women, where she slowly shed a lifelong habit of people pleasing, and where she also transformed the convent culture to allow for expressiveness, warmth, and more straightforward communication"--